A new genus and species of freshwater crab from Madagascar (Decapoda, Brachyura, Potamoidea, Potamonautidae) - Meyer, Kirstin S.; Cumberlidge, Neil; Koppin, Jennifer C. (Zootaxa, 2014)
A new genus and species of freshwater crab is described from Madagascar. The new species is morphologically closest to the three species of the genus Foza Reed & Cumberlidge, 2006, but can easily be distinguished by having a completely smooth carapace with an unarmed anterolateral margin and a mandible with a distinctly shortened anterior lobe. This unusual suite of characters is sufficient to warrant the recognition of a new monotypic genus to accommodate this species.